Highly branched phenolic resin‐grafted silicone rubber copolymer for high efficiency ablation thermal protection coating. Issue 6 (9th August 2019) - Li, Boqian; He, Chen; Cao, Min; Ren, Ying; Wang, Junshan; Lu, Wu
ABSTRACT: Highly branched phenolic resin‐grafted silicone rubber (PGS) was synthesized by grafting allyl ether phenolic resin onto silicone rubber with Si─H groups via hydrosilylation. The chemical structure of the copolymer was characterized by Fourier transform infrared spectroscopy, nuclear magnetic resonance, and gel permeation chromatography, and its microphase morphology was observed via scanning electron microscopy (SEM). The mechanical properties and thermal stability of the material were also characterized. Thereafter, an ablation thermal protection coating (ATPC) based on PGS as the polymer matrix was prepared. In comparison with silicone rubber‐based ATPC, the PGS‐based ATPC showed better thermal stability and a stronger char layer. After oxygen–acetylene testing, the micromorphology and chemical composition of the PGS‐based ATPC were characterized via SEM, energy‐dispersive spectrometry, and X‐ray diffraction. Finally, the PGS‐ and silicone rubber‐based ATPCs were subjected to a heat flow of 370 kW m −2 for 70 s, the background temperature of the PGS‐based ATPC was only 70 °C. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48353. Abstract :